2021
DOI: 10.1097/01.jaa.0000733248.60056.6b
|View full text |Cite
|
Sign up to set email alerts
|

Do PA licensure questions violate the Americans with Disabilities Act?

Abstract: Objective: Negative stigma related to mental health diagnoses is common in both clinicians and the public. Questions about physical and mental conditions on licensure applications often are overly broad and may violate the Americans with Disabilities Act (ADA). This study investigated state physician assistant (PA) licensing applications relating to physical and mental health, and their consistency with the ADA. Methods: We collected PA state licensure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Taken together with our previous data on initial applications (28 consistent for physical health, and 25 consistent for mental health), 18 states were consistent with the ADA with regard to licensure questions about physical and mental health for initial and renewal applications (Figure 2). 6 Thirty-two states were inconsistent with the ADA in at least one application and for at least one of physical and mental health questions; one state (Michigan) was consistent on its initial application but we were not able to obtain the renewal application. A one-way ANOVA confirmed that this difference between perceived risk of repercussions on licensure between physical and mental health issues was signifi cant (P < .05).…”
Section: Study 1 Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Taken together with our previous data on initial applications (28 consistent for physical health, and 25 consistent for mental health), 18 states were consistent with the ADA with regard to licensure questions about physical and mental health for initial and renewal applications (Figure 2). 6 Thirty-two states were inconsistent with the ADA in at least one application and for at least one of physical and mental health questions; one state (Michigan) was consistent on its initial application but we were not able to obtain the renewal application. A one-way ANOVA confirmed that this difference between perceived risk of repercussions on licensure between physical and mental health issues was signifi cant (P < .05).…”
Section: Study 1 Resultsmentioning
confidence: 89%
“…This survey included demographic information about the respondents, as well as two questions used in previous research about help-seeking behavior and licensure concerns for physicians and PAs. 5,6 Data were analyzed using SPSS Version 25. Descriptive statistics were collected and reviewed, followed by analyses to explore the relationship between various demographic (age, sex, specialty) or regulatory (state compliance with the ADA for initial application, renewal application, or both) factors and the likelihood to feel reluctance to seek help for physical or mental health issues due to concerns about unfavorable effects on licensure.…”
Section: Brief Research Report Study 2 Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research in the March 2021 issue of JAAPA highlighted the widespread practice of PA license applications asking deep, probing questions about mental health 7. These intrusive questions do real harm to clinicians and have a paradoxical effect on medical boards' mandate of public safety.…”
mentioning
confidence: 99%